Analisis Kompetensi Petugas Proteksi Radiasi di Fasilitas Radiologi Diagnostik dan Intervensional dari Perspektif Inspektur Keselamatan Nuklir – BAPETEN. - Puji Hastuti; Sjahrul Meizar Nasri; Adi Drajat Noerwarsana (Jurnal Imejing Diagnostik (JImeD), 2021)
Background: Radiation Protection Officer (PPR) plays an important role in ensuring radiation safety supervision in diagnostic and interventional radiology facilities. To support this, high level competencies are absolutely necessary. The purpose of this competency analysis study is to obtain an overview of the competence of radiation protection officers working in diagnostic and interventional radiology facilities. Methods:  This study is a descriptive as well as quantitative research. The study was conducted by collecting primary data through filling out questionnaires with an assessment by 6 inspectors with respondents assessed as 40 PPR from 40 diagnostic radiology facilities spread across West Java, East Java, Batam, Riau Islands. Validity and Reliability testing was carried out in this study. PPR competency level analysis was carried out by testing statistical descriptions and testing the frequency distribution using Statistical Product and Service Solution (SPSS) for windows 21.Results: The results of PPR competence in 40 diagnostic and interventional radiology facilities by 6 Nuclear Safety Inspectors showed that the level of PPR competence in diagnostic radiology facilities was at a high level. This is related to the selection of nuclear safety inspectors who are in the (good) and (very good) rangeConclusion:  Based on the computational analysis using the SPSS version 21 program, it shows that the level of hard competency (technical competency) and soft competency of PPR in diagnostic and interventional radiology facilities is at a level above 3 or the average is at a level close to high. Further research needs to be done with a more comprehensive competency statement item variable and with a larger number of inspectors and PPR with a research time span long enough in order to describe the actual PPR competencies on the field.